Multisystemic Inflammatory Syndrome Temporally Associated with COVID-19 in a Regional Pediatric Hospital from México - Joel Barroso-Santos; Angelina Ingrid Robledo-Martínez; Sara Elva Espinosa-Padilla; Rubén Genaro Hurtado del Ángel; Felipe Arteaga-García; Mónica Langarica-Bulos; José Antonio Madrid-; Beatriz Adriana Sánchez-Reyes; Sarai Eunice Hernández-Cadena; Jorge Iván Suárez-Soto; Carolina Delgado-Amézquita; Brenda Godínez-Hernández; et al. (MDPI AG, 2023)
Multisystemic inflammatory syndrome (MIS-C) is an inflammatory condition temporally associated with COVID-19 in children; nevertheless, the clinical and immunologic spectrum of MIS-C is heterogeneous, and its long-term effects are unknown. During the period of August 2020 to December 2021, a total of 52 MIS-C cases were confirmed in pediatric patients from the Hospital del Niño DIF Hidalgo, diagnosed using criteria from the World Health Organization. All patients had serologic IgG confirmation of SARS-CoV2, the mean age of the patients was 7 years, and 94% of the patients did not have a previous underlying disease. In addition to the presentation of lymphopenia, neutropenia, and thrombocytopenia, elevations in D-dimer and ferritin levels were observed in all patients. There was clinical improvement with intravenous gamma globulin and corticosteroid treatment.